1999
DOI: 10.1046/j.1537-2995.1999.39050522.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection by an unenveloped DNA virus associated with non‐A to ‐G hepatitis in Japanese blood donors with or without elevated ALT levels

Abstract: The detection of TT virus DNA, at a frequency higher in donors with elevated ALT than in those without, strengthens the association of TT virus with non-A to -G hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This may explain why, in several studies conducted with detection methods of limited sensitivity, TTV infection was found more frequently in patients with non-A±E hepatitis than in other individuals [Ikeda et al, 1999;Itoh et al, 1999;Orii et al, 1999]. Because these patients were not at increased risk for parenterally transmitted virus infection, the ®nding might also imply that a sustained TTV replication might be responsible for at least some liver damage and account for a proportion of unexplained chronic hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why, in several studies conducted with detection methods of limited sensitivity, TTV infection was found more frequently in patients with non-A±E hepatitis than in other individuals [Ikeda et al, 1999;Itoh et al, 1999;Orii et al, 1999]. Because these patients were not at increased risk for parenterally transmitted virus infection, the ®nding might also imply that a sustained TTV replication might be responsible for at least some liver damage and account for a proportion of unexplained chronic hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, TTV DNA detectable by N22 PCR was significantly more frequent in the donors with elevated ALT levels than in those with normal levels (22.1 vs. 15.7%, p ! 0.02) [24].…”
Section: Ttv Infection and Liver Injurymentioning
confidence: 99%
“…Primers deduced from noncoding region can detect TTV DNA, irrespective of different genotypes, with a frequency of 190% in the healthy general population in Japan [20]. By contrast, primers deduced from the N22 region in the coding region detect TTV DNA of restricted genotypes, such as genotypes 1 and 2 [5,23], with a prevalence of 10-20% in Japan [5,24] and of only 1-2% in the United States and England [6,7]. Table 2 compares TTV DNA titers of five sera (No.…”
Section: Genomic Heterogeneity Of Ttvmentioning
confidence: 99%
“…Undoubtedly, the above observations rule out the notion that clinically evident liver disease is a frequent consequence of TTV infection. However, the evidence is not totally unequivocal, since data also exist that are compatible with the possibility that, in some cases, transient and mild abnormalities in liver enzyme levels are associated with TTV infection (33,34,56,61,65,68,81,88,110,126). Likewise, in several series of HCV patients, coinfection with TTV appeared to be associated with increased severity of biochemical and histological parameters of liver damage (15,22,48,56,172,175,191).…”
Section: Clinical Significancementioning
confidence: 99%